Correction: Preparation and characterization of activated montmorillonite clay supported 11-molybdo-vanado-phosphoric acid for cyclohexene oxidation. Issue 14 (19th February 2015) - Boudjema, S.; Vispe, E.; Choukchou-Braham, A.; Mayoral, J. A.; Bachir, R.; Fraile, J. M.
<x xml:space="preserve">Abstract</x> Correction for 'Preparation and characterization of activated montmorillonite clay supported 11-molybdo-vanado-phosphoric acid for cyclohexene oxidation' by S. Boudjema et al., RSC Adv., 2015, 5, 6853–6863.